Fragile X-associated tremor ataxia syndrome with co-occurrent progressive supranuclear palsy-like neuropathology - Amanda N. Sacino; Stefan Prokop; Meggen A. Walsh; Jennifer Adamson; S. H. Subramony; Amy Krans; Peter K. Todd; Benoit I. Giasson; Anthony T. Yachnis (Acta Neuropathologica Communications, 2019)
Abstract Co-occurrence of multiple neuropathologic changes is a common phenomenon, most prominently seen in Alzheimer’s disease (AD) and Parkinson’s disease (PD), complicating clinical diagnosis and patient management. Reports of co-occurring pathological processes are emerging in the group of genetically defined repeat-associated non-AUG (RAN)-translation related diseases. Here we report a case of Fragile X-associated tremor-ataxia syndrome (FXTAS) with widespread and abundant nuclear inclusions of the RAN-translation related FMRpolyG-peptide. In addition, we describe prominent neuronal and glial tau pathology representing changes seen in progressive supranuclear palsy (PSP). The highest abundance of the respective pathological changes was seen in distinct brain regions indicating an incidental, rather than causal correlation.